(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
This study aimed to assess the knowledge and attitudes of nursing students regarding anxiety related to examination. Research methods: Descriptive cross-sectional study, which included 81 nursing students (male and female) in level five, six, seven, and eight who are studying at a private university in Jordan, the respondents were selected according to the criteria of inclusion and exclusion, a survey-questionnaire was developed and it was used as instrument for data collection. The questionnaire includes the demographic data and the students’ knowledge and attitudes on examination anxiety followed by analysis of data. Results: The results showed that among the total number of students who participated in the study, majority are female (75.3%), most of their age were between 20 – 22 years old which represented (90.1%) and also majority of respondents know the definition of anxiety which represented (70.4%). Conclusion: This study concluded that nursing students have good knowledge regarding anxiety which represented (65.7%) this study concluded that nursing students have a positive attitude with regard to anxiety on examination which represented (74%). In addition, it was found out that some students have anxiety during examination which represented (8.7%), while other have some signs of anxiety on examination that was represented (75.3%), and 16% of the other respondents have not experienced anxiety during examination.